The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1073/pnas.1114476109
|View full text |Cite|
|
Sign up to set email alerts
|

Polar growth in the Alphaproteobacterial order Rhizobiales

Abstract: Elongation of many rod-shaped bacteria occurs by peptidoglycan synthesis at discrete foci along the sidewall of the cells. However, within the Rhizobiales, there are many budding bacteria, in which new cell growth is constrained to a specific region. The phylogeny of the Rhizobiales indicates that this mode of zonal growth may be ancestral. We demonstrate that the rod-shaped bacterium Agrobacterium tumefaciens grows unidirectionally from the new pole generated after cell division and ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
254
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 198 publications
(283 citation statements)
references
References 40 publications
(34 reference statements)
15
254
0
Order By: Relevance
“…However, in the latter strain the knockout leads to elongated cells. Polar growth has been described for representatives of Rhizobiales, Caulobacterales and Rhodobacterales and may be ancient in Alphaproteobacteria (Brown et al, 2012); the core genes of cell cycle control are conserved throughout the phylum (Brilli et al, 2010). This is the first time that the mode of cell division has been shown to be controlled by QS in Alphaproteobacteria.…”
Section: Discussionmentioning
confidence: 84%
“…However, in the latter strain the knockout leads to elongated cells. Polar growth has been described for representatives of Rhizobiales, Caulobacterales and Rhodobacterales and may be ancient in Alphaproteobacteria (Brown et al, 2012); the core genes of cell cycle control are conserved throughout the phylum (Brilli et al, 2010). This is the first time that the mode of cell division has been shown to be controlled by QS in Alphaproteobacteria.…”
Section: Discussionmentioning
confidence: 84%
“…Indeed, our bioinformatics searches revealed that Agrobacterium and related Rhizobiales species have more genes encoding LD-transpeptidases in their genome than other rod-shaped bacteria that predominantly encode DD-transpeptidases, and LD-transpeptidases are generally insensitive to β-lactam antibiotics (24). That PG biosynthesis in Agrobacterium is distinct is supported by its unique muropeptide profile (4). Also, in contrast to polar growth, midcell PG synthesis before division is significantly affected by Cb and results in striking tire-like expansions at this site.…”
Section: Discussionmentioning
confidence: 88%
“…Finally, cells expressing FtsA-GFP were pulse-labeled with Texas red-X succinimidyl ester (TRSE), which binds cell-surface proteins (4). Following short or long chases in media without TRSE, TRSE remained at the old pole, and FtsA-GFP was at the opposite end of the cell, namely the growth pole ( Fig.…”
Section: Growth Poles and Old Poles Of Agrobacterium Exhibit Differenmentioning
confidence: 99%
See 2 more Smart Citations